ChemInform Abstract: Organic Stereochemistry. Part 5. Stereoselectivity in Molecular and Clinical Pharmacology. Issue 36 (15th August 2013) - Testa, Bernard; Vistoli, Giulio; Pedretti, Alessandro; Caldwell, John
Abstract Review: 169 refs.